Climate change and variability: What are the risks for nutrition, diets, and food systems? - Fanzo, Jessica; McLaren, Rebecca; Davis, Claire; Choufani, Jowel (International Food Policy Research Institute, 2017)
The paper uses a food systems approach to analyze the bidirectional relationships between climate change and food and nutrition along the entire food value chain. It then identifies adaptation and mitigation interventions for each step of the food value chain to move toward a more climate-smart, nutrition-sensitive food system. The study focuses on poor rural farmers, a population especially vulnerable to the adverse effects of climate change on nutrition, although we recognize that there are other vulnerable populations, including urban poor and rural populations working outside of agriculture. Although this report does not explicitly exclude overweight and obesity, it focuses primarily on undernutrition because this nutritional status is currently more prevalent than overnutrition among our target population.